Do firm credit constraints impair climate policy? - Matthias Kaldorf; Mengjie Shi (Deutsche Bundesbank, 2024)
This paper shows that firm credit constraints impair climate policy. Empirically, firms with tighter credit constraints, measured by their distanceto-default, exhibit a relatively smaller emission reduction after a carbon tax increase. We incorporate this channel into a quantitative DSGE model with endogenous credit constraints and carbon taxes. Credit frictions reduce the optimal investment into emission abatement since shareholders are less likely to receive the payoff from such an investment. We find that carbon taxes consistent with net zero emissions are 24 dollars/ton of carbon larger in the presence of endogenous credit constraints than in an economy without such frictions.
Keywords: E44; G21; G28; Q58; 330; Climate Policy; Credit Constraints; Emission Reduction; Corporate Capital Structure; Firm Heterogeneity